Frailty and nutritional inadequacy in older Korean adults: A gender-stratified analysis using National Survey Data - Subeen Kim; Haerang Lee; Minji Kang (PLoS ONE, 2025)
While frailty has traditionally been conceptualized through physical decline, it is increasingly recognized as a complex concept encompassing emotional, psychological, and social factors. This study employed a multidimensional framework to investigate the association between nutritional status and frailty levels across genders. In addition, it aims to provide foundational insights for developing targeted dietary and preventive health policies that support interventions tailored to the characteristics of specific older adult populations. This is a cross-sectional study of the 2009–2020 Korean National Health and Nutrition Examination Survey in 14,242 participants aged 65 and older. The frailty index was constructed using 41 items. Dietary data were obtained through a 24-hour dietary recall, and adequacy of nutrient intake was evaluated based on the Dietary Reference Intakes for Koreans 2020. Multivariable logistic regression analysis was conducted to examine the association between nutritional status and frailty levels. Among participants, 31.6% were categorized as non-frail, 47.8% as pre-frail, and 20.6% as frail. Women exhibited lower total energy intake and higher frailty prevalence than men. Gender-stratified analyses revealed distinct nutritional patterns: frail men showed a significant decreasing trend in riboflavin intake (P-trend = 0.0012), while frail women had increased carbohydrate (P-trend = 0.005) and decreased fat (P-trend = 0.0032) and riboflavin (P-trend = 0.0062) intake. Frailty significantly associated with iron inadequacy in men (OR=1.49, 95% CI:1.15–1.94; P-trend = 0.0018) and riboflavin inadequacy in women (OR=1.45, 95% CI:1.20–1.74; P-trend<0.0001). Frailty in older adults is associated with multidimensional vulnerabilities-including demographic, behavioral, relational, and nutritional factors-with notable gender differences in nutrient intake patterns. These findings underscore the need for gender-specific and integrated nutritional interventions to effectively prevent frailty and improve quality of life in the elderly population.